Male Infertility and Genetic screening: Guidelines in 2021 - Farah, Ghieh; Béatrice, Mandon-Pepin; François, Vialard (Archives of Clinical and Biomedical Research, 2021)
For many years, genetic screening for male infertility was limited to a few analyses: karyotyping, screening for Y microdeletions, and tests for the most frequent cystic fibrosis transmembrane conductance regulator (CFTR) gene variants. The development of new technologies, such as chromosome microarray or new genome sequencing, has broadened access to whole-genome analyses. Over the last decade, many genetic defects have been described, and new strategies seem to emerge. Hence, by focusing on peripheral (rather than central) failures of spermatogenesis, the objectives of the present study were to review the latest data on clinical practice (rather than the physiopathology of these genetic abnormalities) and suggest new guidelines for the genetic screening of male infertility.